Geospatial Celebration of Sidomulyo Village: A Spatial Analysis of Tourist Village Development - Nasobi Niki Suma; Achmad Tedy Hariyanto; Achmad Farichin Zuber; Esti Yulia W.; Khoirotusaniyah Khoirotusaniyah; Nila Rohmatul Ula; Syela Faizah (heritage, 2022)
Sidomulyo Village is on the outskirts of a forest located at the eastern end of Jember Regency, East Java. The village's location, on the outskirts of the forest and surrounded by the Gumitir Mountains, is a challenge in developing this village. In addition, the extended access to the city center has made Sidomulyo Village receive less attention from the district government and investors. A touch of creative and innovative village programs to introduce this village to the broader community needs to be done. One of the program breakthroughs in Sidomulyo Village was a series of activities summarized in the ”Sidomulyo Village Celebration” event. The aims of this study were (1) to find out the objectives and program activities in the "Hajatan Desa Sidomulyo" event, (2) to analyze the spatial reach of the event "Hajatan Desa Sidomulyo", (3) to analyze the positive and negative impacts of the event "Hajatan Desa Sidomulyo". The method used in this research is descriptive qualitative by observing, interviewing, and reviewing necessary research supporting documents. The results showed that the purpose of holding a village celebration was to introduce and build branding in the Sidomulyo Tourism Village. The activity programs for village celebrations include Sidomulyo Tourism Village (STV), Sidomulyo Adventure Trail (SAT), Archipelago Cultural Carnival, National Sheep Contest, Sidomulyo Bersholawat, and Village Celebration Night. The Sidomulyo Village Celebration event geospatially only reached three hamlets: Krajan, Curah Manis, and Curah Damar. Meanwhile, three other hamlets, namely Tanah Manis, Garahan Kidul, and Gunung Gumitir, were not reached or touched by Village Celebration activities. Sidomulyo Village Celebration activities have positively and negatively impacted the development of this village on the outskirts of the forest.